An event-triggered approach to torsional vibration control of drill-string system using measurement-while-drilling data. (January 2021) - Lu, Chengda; Wu, Min; Chen, Luefeng; Cao, Weihua
Abstract: Suppressing torsional vibration of drill-string has great safety and economic importance to drilling process. Note that most existing control methods only measure surface information, their performance are limited, especially for a long drill-string. In this paper, an advanced control system is developed to mitigate torsional vibration of drill-string, using a measurement-while-drilling (MWD) communication tool to collect downhole information. The drill-string is described by a lumped parameter model to include full torsional flexibility modes with less computational complexity. A state observer and a filter are combined to estimate an equivalent control torque to cope with uncertain bit–rock interaction. Considering that the communication and power resources are quite precious for MWD, the downhole state is periodically sampled and an event-triggered mechanism is devised to pick out only some key sampled data for transmission to the surface. Using both the surface continuous measurement and the discrete MWD data with transmission delays, the closed loop of the drill-string and the control system is modeled as a nonlinear time-delay system, based on which sufficient conditions are derived for stability analysis and calculation of gain matrices. A numerical case study is carried out to verify the effectiveness of the approach. Highlights: An event-triggered scheme is devised for measurement-while-drilling communication. A vibration control system is developed using both surface and downhole information. A state observer and a filter are combined to cope with uncertain rock reaction. Delay-dependent practical stability of the closed loop system is analyzed.